2017
DOI: 10.1155/2017/9590803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tranexamic Acid on Hematologic Values and Blood Loss in Reverse Total Shoulder Arthroplasty

Abstract: .Purpose. Use of tranexamic acid (TXA) in the setting of arthroplasty of the lower extremity has been previously described. The aim of this study was to evaluate the benefit of a single dose of TXA (500 mg vial) administered intravenously just prior to RTSA in an Asian population. Methods. The records of 48 patients (no TXA, = 24, versus TXA, = 24) that underwent RTSA for cuff tear arthropathy were retrospectively reviewed. All patients had a Hemovac drain positioned for 2 days after surgery. Hemoglobin (Hb) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…No additional studies were identified from the references of the included studies. After excluding 12 duplicates and 6 studies (two irrelevant topics and four systematic reviews), we finally included the following six studies in this meta-analysis: Abildgaard et al [ 33 ], Friedman et al [ 19 ], Gillespie et al [ 20 ], Kim et al [ 24 ], Pauzenberger et al [ 23 ], and Vara et al [ 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No additional studies were identified from the references of the included studies. After excluding 12 duplicates and 6 studies (two irrelevant topics and four systematic reviews), we finally included the following six studies in this meta-analysis: Abildgaard et al [ 33 ], Friedman et al [ 19 ], Gillespie et al [ 20 ], Kim et al [ 24 ], Pauzenberger et al [ 23 ], and Vara et al [ 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes ranged from 48 to 194, with a total 677 patients (680 shoulders, 343 in the TXA group and 337 in the non-TXA group). Three included studies [ 20 , 23 , 34 ] were RCTs that prospectively compared outcomes, and the other three RCS [ 19 , 24 , 33 ] compared results using retrospective analysis (Table 1 ). Further perioperative characteristics of the included studies are described in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations